Implementação de uma Área de Proteção Ambiental na Baía de Sepetiba, Rio de Janeiro : educação para o ambiente - Pereira, Paula Moraes (1999)
This research aims to evaluate the relationship between the community that lives on the shores of baia de Sepetiba and conservation unit called Environmental Protection Area ( APA das Brisas). The conservation unit s main purpose is to use environmental planning for productive activities, to allow for natural resources conservation. It is necessary to know the social environmental pattern of the community and perform educational activities to implement the unit. The area is privately owned but is overseen by a local authority from Rio de Janeiro City Hall. The activities were held in two public schools, in math and sciences classes with seventy-two students of sixth and seventh grades. Data obtained in schools showed that protected areas are a topic that can be used as environmental sources by teachers to help the discussion about citizenship. The data collected in the local community showed that they did not know the conservation unit, but that neighborhood associations and the administration staff of Rio de Janeiro City Hall could work together to change this scenario.